From short-term surgical missions towards sustainable partnerships. A survey among members of foreign teams. (January 2021) - Botman, M.; Hendriks, T.C.C.; Keetelaar, A.J.; Smit, F.T.C.; Terwee, C.B.; Hamer, M.; Nuwass, E.; Jaspers, M.E.H.; Winters, H.A.H.; Corlew, S.
Abstract: Introduction: An estimated five billion people lack access to safe surgical care across the globe. Traditionally, providing short-term surgical missions has been the main strategy for health professionals from high-income countries to support surgical care in low- and middle-income countries. However, traditional missions have come under criticism because evidence of their sustainable value is lacking, along with any robust documentation and application of recommendations by participants of ongoing surgical missions. Using survey data collection and analysis, this study aims to provide a framework on how to improve the use of visiting surgical teams to strengthen surgical services in resource-poor settings. Method: An online survey was conducted among members of foreign teams to collect data on five specific areas: basic characteristics of the mission, main activities. Follow-up and reporting, the local registration process and collaboration with local actors. The survey included 58 respondents from 13 countries, and representing 20 organizations. Results: During surgical missions, training activities were considered most impactful, and reporting on outcome/s, along with long-term follow-up was strongly recommended. According to almost all participants (94%), the focus should be on establishing collaborative practices with local actors, and encourage strategic, long-term changes under their leadership. Conclusion: Building sustainable partnerships within local healthcare systems is the way forward for foreign surgical parties that aim to improve surgical care in low- and- middle income countries. When foreign help is offered, local stakeholders should be in the lead. Highlights: Members of visiting surgical teams call for more collaboration to improve surgical care in low-and middle-income countries. The traditional surgical mission model should move towards sustainable partnerships with local actors in the lead. When foreign help is needed its recommended to focus on teaching activities and to evaluate outcomes.